1995
DOI: 10.1046/j.1471-4159.1995.64052125.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Gabapentin, a γ‐Amino Acid Drug, by System L α‐Amino Acid Transporters: A Comparative Study in Astrocytes, Synaptosomes, and CHO Cells

Abstract: The system L transporter is generally considered to be one of the major Na+‐independent carriers for large neutral α‐amino acids in mammalian cells. However, we found that cultured astrocytes from rat brain cortex accumulate gabapentin, a γ‐amino acid, predominantly by this α‐amino acid transport system. Uptake of gabapentin by system L transporter was also examined in synaptosomes and Chinese hamster ovary (CHO) cells. The inhibition pattern displayed by various amino acids on gabapentin uptake in astrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 0 publications
3
102
0
Order By: Relevance
“…Thus, it could be supposed that spinal GABA receptors may not be directly involved in the antinociceptive effect of intrathecal gabapentin. It has been proposed that gabapentin crosses several membrane barriers in the body via a specific amino acid transporter and competes with leucine, isoleucine, valine, and phenylalanine for transport (1,7). However, intrathecal L-leucine and BCH did not antagonize the antiallodynic effect of intrathecal gabapentin (24).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could be supposed that spinal GABA receptors may not be directly involved in the antinociceptive effect of intrathecal gabapentin. It has been proposed that gabapentin crosses several membrane barriers in the body via a specific amino acid transporter and competes with leucine, isoleucine, valine, and phenylalanine for transport (1,7). However, intrathecal L-leucine and BCH did not antagonize the antiallodynic effect of intrathecal gabapentin (24).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that doses lower than 1,200 mg do not reach the therapeutic plasma levels needed to produce clinical anxiolytic effects. 31,32 Furthermore, the documentation of preoperative anxiety prior to enrolment was not undertaken in previous work. 9,10 Biopsychosocial models have suggested that psychological outcomes must be considered in addition to physical outcomes in order to understand pain-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin not only binds a 2 d, but is also a substrate for active transport, believed to enter into the CNS by the system L amino-acid transporter (Su et al, 1995(Su et al, , 2005. To improve bioavailability without relying on an active transport mechanism, acid bioisosteres (a substituent or group that imparts similar biological properties to a chemical compound, but enhances the physical properties for drug development) and prodrugs have been employed (Field et al, 2007).…”
Section: Voltage-gated Ion Channels: Novel Approaches To Modulation Omentioning
confidence: 99%